Comparación de las medidas de la dimensión vertical en reposo y de la distancia ojo-oreja de hombres y mujeres dentados entre 18- 29 años de edad en la Universidad de las Américas en Ecuador - Canelos Cruz, Paola Stephanie (2016)
The vertical dimension in the toothless is a relevant parameter for the recuperation of the relationship that exists between the maxillary and the jaw, what will allow us to get back the stomatology and esthetic functions. This facial proportion varies in every person and that why this become into a challenge to the dentist, because they do not have the intention to cause any danger to the patient. If it is in a bad position we will have some problems even if there be an increase or a decrease of the measure. Some investigations show the difference between women and men, but no one of them are focus on the Vertical Dimension part, and other ones that are focus on the Vertical Dimension but not interested in discovering if a difference between genders exists; and that's why the decision of execution is investigated to give an answer to this unknown if both are equal or they have some difference In this study we achieve to show the difference that exists between genders in the symmetry face and the difference that exists in this measure, we took a sample of 260 young people, and we divided in 130 women and 130 men from 18 - 29 years old which were students of odontology at the Universidad de las Americas in Quito- Ecuador. We took 3 pictures: one of the front, one of the left and other one of the right. Analyzing the statistical results between the two genders, it show us that men are closer than women to the Vertical Dimension measurement; women had a difference of 6 mm on the right side and 7 mm on the left side.